Vampires and a Reasonable Dictionary - Abbot, Scott (punctum books, 2014)
As a follow-up to their first collaboration Repetitions (published in Belgrade in 1994, and in English by punctum in 2013), in 2008 the authors published, also in Belgrade, Vampiri & Razumni recnik, published here by punctum as Vampires & A Reasonable Dictionary. Vampires is Radaković's fictionalized account of a Serb living in Cologne, Germany while his former country disintegrates. He travels in the American West, ostensibly looking for the vampires causing chaos in his own country, and then returns to Europe, having found no vampires. It is a dark text, a story of destruction told in a narrative that refuses all the solaces narrative has traditionally afforded. A Reasonable Dictionary is Abbott's personally troubled account of his and Radaković's trip up the Drina River between the civil wars, a journey made with the novelist Peter Handke, a trip during which some of Abbott's specifically American stories lost their moral structure.